2019
DOI: 10.1055/s-0039-1688841
|View full text |Cite
|
Sign up to set email alerts
|

Medial Patellofemoral Ligament Reconstruction in Traumatic Patellar Dislocation without Patellar Fixation

Abstract: Acute traumatic patellar dislocation is a common injury, and spontaneous reduction may occur at the time of injury or may be reduced at the field of the accident by someone. It may be associated with osteochondral fractures and rupture of medial patellar stabilizers leading to recurrent patellar instability. The aim of this prospective study was to evaluate the outcomes of medial patellofemoral (PF) ligament (MPFL) reconstruction in recurrent traumatic patellar dislocation. Forty-five patients presented with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Several different techniques for patellar graft fixation have been reported [7, 15, 21, 29, 30]. A commonly used patellar graft fixation technique requires the creation of transverse patellar bone tunnels for implant‐free patellar MPFL graft fixation [9, 17, 26, 34]. However, patellar bone tunnel techniques for patellar MPFL graft fixation are at increased risk of postoperative patellar fracture [5, 7, 26, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Several different techniques for patellar graft fixation have been reported [7, 15, 21, 29, 30]. A commonly used patellar graft fixation technique requires the creation of transverse patellar bone tunnels for implant‐free patellar MPFL graft fixation [9, 17, 26, 34]. However, patellar bone tunnel techniques for patellar MPFL graft fixation are at increased risk of postoperative patellar fracture [5, 7, 26, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with traumatic MPFL injury and RPI without elevated TT-TG distance, significant patella alta, or trochlear dysplasia can be expected to achieve good clinical outcomes after treatment with either MPFL-R or ET alone. 13,25 However, it has been reported that isolated MPFL-R should be avoided for the treatment of RPI in the setting of significant patella alta and an elevated TT-TG distance. [20][21][22] If this is so, what is the appropriate procedure to perform in addition to MPFL-R?…”
Section: Discussionmentioning
confidence: 99%